Project manager attributes influencing project success in the South African construction industry - Gewanlal, Colin; Bekker, Michiel (University of the Free State, 2015)
The South African construction industry has suffered the loss of many qualified middle-management-level project managers in recent years. This has resulted in many young, inexperienced project managers being forced to manage large complex projects. In addition, senior project managers, who are still practising locally, are too busy to mentor and guide the younger project managers, due to the shortage of professionals in the local industry. This article reports on a study done to identify the most important attributes that influence project success in the South African construction industry, by extracting a list of factors identified in the existing literature and grouping these factors into six main categories. Each category contains six factors. A questionnaire was compiled and distributed via an online survey tool. The data was analysed using statistical methods including concordance and correlation. The results indicated that ‘interpersonal factors’ was considered the most important category, followed by ‘application of theory’. ‘Personal contribution’ and ‘personal character’ were considered the least important categories. However, the most important attributing factors were ‘communication skills’ and ‘leadership style’, neither of which was listed under the top two categories. In general, a low level of concordance was achieved, confirming the belief that level of knowledge, experience and mutual agreement among participants in the industry is low.

Die Suid-Afrikaanse konstruksiebedryf het in die afgelope paar jaar baie gekwalifiseerde middel-bestuursvlak projekbestuurders verloor. Dit het daartoe gelei dat baie jong, onervare projekbestuurders gedwing word om groot komplekse projekte te bestuur. Hierdie artikel rapporteer die resultate van ŉ studie gedoen om die belangrikste faktore wat die projeksukses in die Suid-Afrikaanse konstruksiebedryf beïnvloed, te identifiseer. ŉ Literatuurstudie is gedoen om die belangrikste suksesfaktore te bepaal en in ses kategoriëe te groepeer. Elke kategorie bevat ses faktore. ‘n Vraelys is saamgestel en aanlyn gestuur aan moontlike deelnemers. Die data is ontleed met behulp van statistiese metodes, insluitend konkordansie en korrelasie. Die resultate het getoon dat die belangrikste kategorie was ‘interpersoonlike faktore’, gevolg deur ‘toepassing van teorie’. ‘Persoonlike bydrae’ en ‘persoonlike karakter’ is beskou as die kategoriëe met die minste impak. Die belangrikste faktore vir projeksukses was ‘kommunikasievaardighede’ en ‘leierskapstyl’, waarvan beide nie onder die top twee kategoriëe verskyn nie. Oor die algemeen is ‘n lae vlak van konkordansie bereik wat bevestig dat die vlak van kennis, ondervinding en eenstemmingheid tussen deelnemers in die industrie baie laag is.
Keywords: Project manager attributes; Project experience; Construction management; Project manager profiles